SISTEM PEMIDANAAN DALAM BIDANG PERBANKAN - Hermanita, Hermanita (ISTINBATH JURNAL HUKUM, 2004)
Rule of Crime or banking crime system represent special shares (sub system) from overall of crime system. This means banking crime system have to integrate in (consistence with) general law (rules general). Require to conduct of repair/change crime system in legislation banking area, for example: qualification doing an injustice; doing an injustice subject and corporation crime responsibility; sanction type and formulation of sanction; amount of/the duration crime; weight comparison (minimum/maximum) serve a sentence with fine have to consistence. For a while not yet been made a change by legislation hence practice is straightening of law properly cope to fill insuffiency/existing weakness by innovate and construction punish pursuant to law logic, law science doctrines and theory, opinion all expert.Â Keyword: crime system, doing an injustice qualification, doing an injustice subject, crime responsibility.